(untitled) (Revista Contexto & Saúde, 2023)
The objective was to evaluate the microbiological quality and pH of ground beef sold in supermarkets in southern Bahia, Brazil. Sample collection and preparation of "ground meat" were carried out in which the pH was measured and microbiological analyzes were carried out to count mesophilic aerobic bacteria, molds and yeasts, developed from the Most Probable Number (MPN) of total coliforms and Coliforms at 45ºC or thermotolerant, Escherichia coli test, Salmonella test and coagulase-positive Staphylococcus count. The most likely number of total coliforms ranged from 21 to 2.7 x 104 MLN/g (mean 3.5x103 MPN/g), and coliforms at 45ºC or thermotolerant coliforms from <3 to 5 x 103 MPN/g (mean 1. 3x103 MPN/g). The presence of Escherichia coli was confirmed in 70% of the samples. The presence of Salmonella was not detected in any of the samples, and positive Staphylococcus coagulase was <100 CFU/g in all samples present. All ground beef samples had a pH between 5.5 and 7.